A legal study on the protection of child abuse in Malaysia / Munirah Azman...[et al.] - Azman, Munirah; Ridzwan, Intan Nabila; Khairuddin, Siti Aisyah; Muhamad Isa, Noor' Ain (Faculty of Law, 2013)
The focus of this legal study is to examine the current legal provisions conferred under the Child Act 2001 (Act 611), Law Reform (Marriage and Divorce) Act 1976 (Act 164) and Domestic Violence Act 1994 (Act 521) regarding the protection of child abuse in Malaysia. This is done with the purpose to identify the weaknesses and problems of protection of child abuse prior to the current legal provisions under these three statutes mentioned above. To enable this legal study to be more precise, the comparison has been made between Malaysia and Australia regarding the law on the protection of child abuse. Since each province in Australia has different significance law, the province of Northern Territory had been selected to be referred to because it has expansive legislation of the entire jurisdiction compared to other provinces. The law on the protection of child abuse in Northern Territory is the Care and Protection of Children Act 2007 (NT). The outcome obtained from the legal study is that the current legislations on the protection of child abuse in Malaysia had shown some weaknesses which must be covered in providing a maximum protection for the children from being maltreated. Therefore, several reforms is recommended in this legal study to improvise the current legislations governing the child abuse in Malaysia.